Sevoflurane exposure induces neurotoxicity by regulating mitochondrial function of microglia due to NAD insufficiency - Zhu, Ruilou; Zeng, Shuang; Li, Ningning; Fu, Ningning; Wang, Yangyang; Miao, Mengrong; Yang, Yitian; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Cellular Neuroscience, 2022)
Developmental neuron received with sevoflurane for several times, the commonly used inhalational anesthetic agent in clinical surgery, tend to be destroyed. Microglia, the resident immune cells of the central nervous system (CNS), are activated after sevoflurane exposure, accompanied by releasing pro-inflammatory cytokines that damage developing neuron. The sevoflurane-induced neurotoxicity could be attributed to activated microglia presenting pro-inflammatory and anti-inflammatory function. Pro-inflammatory microglia release cytokines to impair the CNS, while anti-inflammatory microglia engulf damaged neurons to maintain CNS homeostasis. Sevoflurane exposure promotes the secretion of pro-inflammatory cytokines by microglia, while inhibit microglial phagocytic function. Microglia with poor phagocytic function cannot engulf damaged neurons, leading to the accumulation of damaged neurons. The mechanism underlying poor phagocytic function may be attributed to mitochondrial dysfunction of microglia induced by sevoflurane exposure, in which affected mitochondria cannot generate adequate ATP and NAD to satisfy energy demand. We discovered that sevoflurane treatment impaired the mitochondrial metabolism of microglia, which resulted in NAD deficiency and couldn’t product sufficient energy to clear damaged neurons to maintain CNS development. Our findings provide an explanation of a new mechanism underlying sevoflurane-induced neurotoxicity.